Catkin frost damage in Mediterranean cork-oak (Quercus suber L.). - García-mozo, Herminia; Hidalgo, Pablo J.; Galán, Carmen; Gómez-Casero, Maria Teresa; Domínguez, Eugenio (Israel Journal of Plant Sciences, 2001)
During a period of study of floral phenology and pollen production in the cork-oak, Quercus suber L. (199799), an interruption of catkin development was detected in spring 1998. The cause might have been a sharp drop in minimum temperatures during that period, which coincided with the initial stages of microsporogenesis. Results show that environmental temperatures close to 0 ºC halted microsporogenesis and catkinelongation, resulting in their complete death. No fruits were observed in the affected zone, as a possible consequence of the lack of pollen. Phenological, histological, andaerobiological data are analyzed as a whole in order to gain a better understanding of the phenomenon. Cold spells during flowering may be one of the factors influencing the high interannual variability of acorn production in Quercus species. [ABSTRACT FROM AUTHOR]
Keywords: CATKIN-bearing plants; Cork oak; flowers; Fruit; Phenology; PLANT spores; POLLEN (citation)

Catkin frost damage in Mediterranean cork-oak (Quercus suber L.). - García-mozo, Herminia; Hidalgo, Pablo J; Galán, Carmen; Gómez-Casero, Maria Teresa; Domínguez, Eugenio (Israel Journal of Plant Sciences, 2001)
During a period of study of floral phenology and pollen production in the cork-oak, Quercus suber L. (199799), an interruption of catkin development was detected in spring 1998. The cause might have been a sharp drop in minimum temperatures during that period, which coincided with the initial stages of microsporogenesis. Results show that environmental temperatures close to 0 ºC halted microsporogenesis and catkinelongation, resulting in their complete death. No fruits were observed in the affected zone, as a possible consequence of the lack of pollen. Phenological, histological, andaerobiological data are analyzed as a whole in order to gain a better understanding of the phenomenon. Cold spells during flowering may be one of the factors influencing the high interannual variability of acorn production in Quercus species. [ABSTRACT FROM AUTHOR]
Keywords: CATKIN-bearing plants; Cork oak; flowers; Fruit; Phenology; PLANT spores; POLLEN (citation)